Focus on fertilizers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The role of plant nutrients for sustainable food crop production in sub-Saharan Africa edited by H van Reuler and W H Prins 1993 232pp ISBN 90 801673 12 Pbk VKP PO Box 443 2260 AK Leidschendam THE NETHERLANDS